PENERAPAN CRM DENGAN SISTEM INFORMASI BERBASIS WEB UNTUK KEPUASAN PELANGGAN - Toni Kusnandar (Jurnal Computech & Bisnis (e-Journal), 2015)
At this time a lot of services the retailer presents his wares in cyberspace. The customer does not need to be pampered to move from its place if when they were working, relaxing at home, or even when the customers are on vacation, as long as they get an internet connection so they can view, compare and make decisions that ultimately what goods they buy. Customers are increasingly selective and increasing their comfort standards so that it becomes a challenge for businesses to provide services to meet the needs of its customers in an attempt to survive in a competitive competition in the world of business. In an effort to improve service to its customers, business organizations have a lot of implementing Customer Relationship Management by utilizing the WEB -based information systems. Generally CRM on the market of e - commerce Business to Customer in an effort to improve customer satisfaction requires careful planning of how the service will be provided to customers by considering the quality of the service, the level of trust that will be obtained, the level of security to be provided and Tertiary comfort will be offered, in order to customers feel comfortable and will always come back to the WEB site is provided for the purpose of it all. Keywords: Customer Relationship Management, e-Commerce, WEB site, Customer Satisfaction AbstrakPada saat ini banyak sekali layanan para peritel menyajikan barang dagangannya di dunia maya. Para pelanggan dimanjakan untuk tidak perlu beranjak dari tempatnya apakah ketika mereka tengah bekerja, santai dirumah, atau bahkan ketika para pelanggan sedang berlibur, selama mereka mendapatkan koneksi internet maka mereka dapat melihat, membandingkan dan membuat keputusan barang apa yang akhirnya mereka beli. Para pelanggan semakin hari semakin selektif dan standar kenyamanan mereka terus meningkat sehingga menjadi tantangan bagi para pelaku bisnis untuk menyajikan layanan yang dapat memenuhi kebutuhan para pelanggannya dalam upaya bertahan dalam persaingan yang kompetitif didunia usaha. Dalam upaya meningkatkan layanan kepada para pelanggannya, organisasi bisnis telah banyak menerapkan Customer Relationship Management dengan memanfaatkan sistem informasi berbasis WEB. Umumnya CRM pada pasar e-commerce Business to Customer dalam upaya meningkatkan customer satisfaction memerlukan perencanaan yang matang tentang bagaimana layanan akan diberikan kepada customer dengan mempertimbangkan mutu layanan, tingkat kepercayaan yang akan diperoleh, tingkat keamanan yang akan diberikan serta tingakat kenyamanan yang akan ditawarkan, agar customer merasa nyaman dan akan selalu kembali kepada WEB site yang disediakan untuk keperluan itu semua. Kata Kunci : Customer Relationship Management, e-Commerce, WEB site, Customer Satisfaction